2008
DOI: 10.1002/dmrr.872
|View full text |Cite
|
Sign up to set email alerts
|

Effects of androgens on insulin action in women: is androgen excess a component of female metabolic syndrome?

Abstract: Hyperinsulinemia as a consequence of insulin resistance causes hyperandrogenemia in women. The objective was to review evidence for the converse situation, i.e. whether androgens adversely influence insulin action. Androgen excess could potentially contribute to the pathogenesis of insulin resistance in women with polycystic ovary syndrome (PCOS), metabolic syndrome/type 2 diabetes, and in obese peripubertal girls. An Entrez-PubMed search was conducted to identify studies addressing the relationship of androge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
88
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(98 citation statements)
references
References 168 publications
(168 reference statements)
3
88
0
1
Order By: Relevance
“…Animal models have also shown that prenatal testosterone exposure can induce insulin resistance in early postnatal life [36]. Apter reported that adolescents with functional ovarian hyperandrogenism exhibit disproportionate, early pubertal increases in mean serum insulin levels [37] and Carbould showed that testosterone administration to female rats caused insulin resistance in the skeletal muscles and the adipocytes of women in vitro [20]. Importantly, results of our study keep in track with above observations by showing a significant dependence of the HOMA-IR values on the serum testosterone levels in the PCOS patients (b = 0.498, p = 0.049), which imply that hyperinsulinemia plays a critical intermediary role in androgen induced follicular abnormalities that are the hallmark of the disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Animal models have also shown that prenatal testosterone exposure can induce insulin resistance in early postnatal life [36]. Apter reported that adolescents with functional ovarian hyperandrogenism exhibit disproportionate, early pubertal increases in mean serum insulin levels [37] and Carbould showed that testosterone administration to female rats caused insulin resistance in the skeletal muscles and the adipocytes of women in vitro [20]. Importantly, results of our study keep in track with above observations by showing a significant dependence of the HOMA-IR values on the serum testosterone levels in the PCOS patients (b = 0.498, p = 0.049), which imply that hyperinsulinemia plays a critical intermediary role in androgen induced follicular abnormalities that are the hallmark of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Studies demonstrated positive correlations between insulin and androgen levels [5,18] and such correlations existed in both obese and non-obese PCOS women [19]. Although, it is widely accepted that hyperinsulinemia due to insulin resistance causes hyperandrogenism, studies undertaken with reverse aim showed that testosterone administration caused insulin resistance in skeletal muscle of female rats and in adipocytes of women in vitro [20]. On the other hand, the results of some studies suggested that these two conditions might be two separate entities [18].…”
mentioning
confidence: 99%
“…First, androgens stimulate the hypertrophy of adipocytes by affecting the expression of enzymes and proteins involved in lipid and carbohydrate metabolism, in oxidative stress and in the differentiation of pre-adipocytes into mature adipocytes (42). Secondly, androgens regulate lipolysis, resulting in an increased release of free fatty acids (46). These and other still undefined effects of even modest androgen excess in women may explain the association between visceral fat enlargement and PCOS status in both adolescent and adult women.…”
Section: Arguments In Favor Of the Definition Of Secondary Pcosmentioning
confidence: 99%
“…In addition, there is a general consensus that in most women with PCOS, a mild-tomoderate insulin resistance may be responsible for the high prevalence of the metabolic syndrome (39) and that insulin sensitizers, such as metformin, may improve total and free testosterone in these women (1,8). Notably, it should also be recognized that there has been uncertainty as to whether insulin resistance in PCOS has unique characteristics, since androgen excess per se may explain the development of insulin resistance in the insulin-sensitive tissues, such as fat, muscles and liver (46). In any case, the role of severe insulin resistance and very high circulating insulin in determining the PCOS phenotype in patients with SSIR states is confirmed on both clinical and basic research studies (69).…”
Section: Severe Insulin-resistant Syndrome and Pcosmentioning
confidence: 99%
“…On the other hand, peripheral conversion of androgens to estrogen in adipose tissue inhibits gonadotrophin secretion [39]. Increased androgens in turn contribute to 'apple' and not 'pear' shaped obesity [44,45]; thus, a vicious circle evolves, where abdominal fat accumulation increases insulin resistance and androgen production, with hyperandrogenemia promoting hyperinsulinemia and so forth [46,47].…”
Section: What Is the Fertility Response To Obesity?mentioning
confidence: 99%